Accelerated 3D‐GRASE imaging improves quantitative multiple post labeling delay arterial spin labeling - Boland, Markus; Stirnberg, Rüdiger; Pracht, Eberhard D.; Kramme, Johanna; Viviani, Roberto; Stingl, Julia; Stöcker, Tony (Magnetic resonance in medicine, 2018)
Purpose To investigate the impact of accelerated, single‐shot 3D‐GRASE acquisition on quantitative arterial spin labeling (ASL) with multiple and single post‐labeling delay (PLD) in terms of perfusion‐weighted SNR per unit scan time (TSNRPW) and quantification accuracy. Methods Five subjects were scanned on a 3T MRI scanner using the pseudo‐continuous arterial spin labeling (PCASL) technique with a 3D‐GRASE imaging sequence capable of parallel imaging acceleration. A 3‐inversion pulse background suppression was simulated and implemented in the sequence. Three time‐matched single PLD measurements, a segmented one without acceleration, 1 with conventional GRAPPA, and 1 with CAIPIRINHA sampling, were used to compare TSNRPW. Three time‐matched multiple PLD measurements with the identical imaging parameters were additionally evaluated (no acceleration vs. CAIPIRINHA sampling vs. CAIPIRINHA sampling with doubled number of PLDs). Cerebral blood flow and arterial transit time fit uncertainties were compared and used as a quality measure. Results The single PLD measurements show an 11% TSNRPW increase using CAIPIRINHA sampling instead of GRAPPA sampling, while the non‐accelerated scan exhibits 35% higher TSNRPW compared to the GRAPPA scan. However, taking advantage of the increased number of averages for multiple PLD acquisitions, a 14%/16% (gray matter) and 34%/36% (white matter) reduction of CBF fit uncertainty is observed with CAIPIRINHA sampling (6 PLDs/12 PLDs) compared to no acceleration. Conclusion Accelerated single‐shot 3D‐GRASE with PCASL allows for smaller quantification uncertainties than time‐matched segmented acquisitions. Corresponding single‐shot acquisitions with acceptable blurring and no intra‐volume motion render state‐of‐the‐art ASL methods in a clinically feasible time possible.